2017
DOI: 10.1177/1069072717748957
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Career Aspirations Among Young Men

Abstract: The purpose of this study was to investigate the psychometric properties of a measure of career aspirations for use with college men (i.e., the Career Aspiration Scale–Revised [CAS-R]). Two studies were conducted to assess the psychometric properties of the CAS-R with a total of 414 undergraduate men. The results of the confirmatory factor analysis indicated that the three-factor solution assessing achievement, leadership, and educational aspirations had adequate model fit. Furthermore, when the CAS-R was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The findings confirmed that education aspirations are one of the factors in understanding career aspirations among the younger generations [22,23]. As such, the educational aspiration presented in the 21 st century learning has become one of the aims of this research to look at the needs of the national education aspiration.…”
supporting
confidence: 68%
“…The findings confirmed that education aspirations are one of the factors in understanding career aspirations among the younger generations [22,23]. As such, the educational aspiration presented in the 21 st century learning has become one of the aims of this research to look at the needs of the national education aspiration.…”
supporting
confidence: 68%
“…To assess the career aspirations of women in the United States, O'Brien [27] developed the Career Aspiration Scale (CAS), which has been revised as the CAS-R to provide better psychometric properties and to assess leadership, achievement, and educational aspirations [28]. CAS and CAS-R have been implemented in varied studies, for example: in Chinese schools [29], with Korean students [30,31], in Indonesian high schools [32,33], in US colleges [23,34,35], Pakistani colleges [36], with Indian adolescents [37], with collegeeducated Indian women [38], in a Thai university [7,13], in Thai secondary schools [39], Omani schools [2], and Chinese colleges [40]. Although the CAS-R has demonstrated adequate reliability and validity and has also been proven valid in various contexts, factor structure and psychometric properties have not been consistent across studies.…”
Section: Introductionmentioning
confidence: 99%